Remote Teaching Doesn’t Come Without Challenges - Almodóvar-López, Mayra (2020)
Analysis of challenges faced by early childhood education teachers of 3 to 6 years old as a result of the suspension of face-to-face educational services due to COVID-19, and the implications in teacher education and professional development.